Solve for F 3(F+4)=5F-2

Math
3(F+4)=5F-2
Simplify 3(F+4).
Tap for more steps…
Apply the distributive property.
3F+3⋅4=5F-2
Multiply 3 by 4.
3F+12=5F-2
3F+12=5F-2
Move all terms containing F to the left side of the equation.
Tap for more steps…
Subtract 5F from both sides of the equation.
3F+12-5F=-2
Subtract 5F from 3F.
-2F+12=-2
-2F+12=-2
Move all terms not containing F to the right side of the equation.
Tap for more steps…
Subtract 12 from both sides of the equation.
-2F=-2-12
Subtract 12 from -2.
-2F=-14
-2F=-14
Divide each term by -2 and simplify.
Tap for more steps…
Divide each term in -2F=-14 by -2.
-2F-2=-14-2
Cancel the common factor of -2.
Tap for more steps…
Cancel the common factor.
-2F-2=-14-2
Divide F by 1.
F=-14-2
F=-14-2
Divide -14 by -2.
F=7
F=7
Solve for F 3(F+4)=5F-2

Solving MATH problems

We can solve all math problems. Get help on the web or with our math app

Scroll to top